School Law Enforcement Officer Perceptions of Developmentally Oriented Training. (4th August 2021) - Scheuermann, Brenda; Billingsley, Glenna; Dede-Bamfo, Ohenewaa; Martinez-Prather, Kathy; White, Shawna R
Abstract: School-based policing, one of the fastest-growing areas of law enforcement, requires unique skills and presents unique challenges. Specialized training for school resource officers (SROs) is encouraged by the US Departments of Education and Justice (2016) and states are increasingly making available or requiring SROs to complete training designed to better prepare them for school settings. In 2016, Texas mandated a comprehensive, 16-h training programme for SROs from moderate and large school districts. In this paper, we describe a survey conducted to assess perceptions of the first class of SROs to complete that training. We describe SROs' perceptions of the quality and content of the training, need for the training, and the self-reported impact of training on officers' daily job activities. Based on the largely positive responses and comments from over 400 SROs, we provide recommendations for policy makers considering similar specialized training for SROs.